Aperçu Sur La Place De La Demarche D’investigation En Sciences Experimentales Dans L’enseignement Du Secondaire Qualifiant Cas De L’academie De La Ville De Fes - Ihsane Kouchou; Fatiha Kaddari; Nezha Bennis; Rida Hajji Hour; Asmae Bouayad (European Scientific Journal, ESJ, 2017)
The investigative approach (DI) demonstrates more and more its potential in teaching. Indeed, it enables students to develop skills, attitudes and interests, which are necessary to live in a society increasingly dependent on the applications of science. This study falls within the framework of research studies questioning the application of the investigative approach in the teaching of science in Morocco. In this work, we aim to highlight the representations of secondary school teachers about the concept of investigative approach, see whether this approach is adopted or not in the teaching of experimental sciences disciplines (Science of life and earth, Science of physics and chemistry) and determine the constraints and the obstacles to its implementation. In order to achieve these objectives, a questionnaire was drawn up and was the subject of an exploratory study among 45 teachers of experimental sciences practicing in different secondary schools in Fez city. The results of this survey reveal, firstly, that the teachers questioned seem to have confusions about the investigation process and secondly, they highlight the presence of a set of constraints and difficulties which prevent its application in the classroom.